Peptide allergen‐specific immunotherapy for allergic airway diseases—State of the art. Issue 6 (17th February 2021) - Wraith, David C.; Krishna, Mamidipudi T.
Abstract: Allergen‐specific immunotherapy (AIT) is the only means of altering the natural immunological course of allergic diseases and achieving long‐term remission. Pharmacological measures are able to suppress the immune response and/or ameliorate the symptoms but there is a risk of relapse soon after these measures are withdrawn. Current AIT approaches depend on the administration of intact allergens, often comprising crude extracts of the allergen. We propose that the challenges arising from current approaches, including the risk of serious side‐effects, burdensome duration of treatment, poor compliance and high cost, are overcome by application of peptides based on CD4 + T cell epitopes rather than whole allergens. Here we describe evolving approaches, summarize clinical trials involving peptide AIT in allergic rhinitis and asthma, discuss the putative mechanisms involved in their action, address gaps in evidence and propose future directions for research and clinical development.